Up-to boundary regularity for a singular perturbation problem of p-Laplacian type equations in non-divergence form. (November 2019) - Ricarte, Gleydson C.; Araújo, Janielly G.
Abstract: We prove interior and up to boundary Lipschitz regularity of the viscosity solutions to a singular perturbation problem for a reaction–diffusion equation related to the normalized p -Laplacian equation.